The collision model of the Crimean orogen - the experience of the finite element method - V. V. Gonchar (Геофизический журнал, 2013)
Finite elements method is attracted for numerical modeling of crust deformation of Crimea Mountains within hypothesis of its collisional formation. Elastic and elastoplastic (Coulomb) ap-proaches are used. As a result next basic positions of collisional model are proved: 1) localized indenter compression of margin of Scythian plate from side of East Black Sea basin; 2) lateral extru-sion of south-west part of orogen; 3) ramp-obductional mechanism of interacting crust microplate with continental margin. Seismicity is explained as localization of plastic deformation in set of restricted subduction of mantle lithosphere and owerthrusting crust plate. Gravitational maximum within south-west margin of Crimea Mountains is connected to extensional zone of extrusive block, Alushta-Batun zone of magnetic anomalies is regarded as manifestation of crustal indenter moving responsible for collisional setting in Crimea.